2020
DOI: 10.1016/j.omtn.2020.07.031
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: MicroRNA-410-3p Binds to TLR2 and Alleviates Myocardial Mitochondrial Dysfunction and Chemokine Production in LPS-Induced Sepsis

Abstract: Mitochondrial dysfunction and chemokine production have been reported to be involved in the pathogenesis of sepsis. Our initial bioinformatics analysis identified differentially expressed TLR2 in sepsis and the upstream regulatory microRNA-410-3p (miR-410-3p). Hence, the current study was performed to characterize the potential mechanism by which miR-410-3p modulates mitochondrial dysfunction and chemokine production in lipopolysaccharide (LPS)-induced mice in vivo and cardiomyocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“… 29 , 30 In a previous investigation, the decreased miR-410-3p expression is predictive in the sepsis mice models. 31 Furthermore, our report discovered the levels of miR-410-3p were reduced in the NS group and this trend was reversely associated with the relative expression of NORAD, substantiating NORAD might target miR-410-3p in the regulation of NS development. One of the limitations in our subject was that we did not include healthy patients and compare the expression between healthy controls and NS neonates.…”
Section: Discussionmentioning
confidence: 51%
“… 29 , 30 In a previous investigation, the decreased miR-410-3p expression is predictive in the sepsis mice models. 31 Furthermore, our report discovered the levels of miR-410-3p were reduced in the NS group and this trend was reversely associated with the relative expression of NORAD, substantiating NORAD might target miR-410-3p in the regulation of NS development. One of the limitations in our subject was that we did not include healthy patients and compare the expression between healthy controls and NS neonates.…”
Section: Discussionmentioning
confidence: 51%
“…Previously it was disclosed that miR-410-3p acted as a protector in hypoxia-induced cardiomyocyte injury [ 31 ]. In line with this, overexpression of miR-410-3p was also suggested a potential therapy for sepsis-induced myocardial injury [ 18 ]. In spite of that, a recent study, however, showed that miR-410-3p aggravated hypoxia/reoxygenation-induced cardiac injury [ 17 ].…”
Section: Discussionmentioning
confidence: 96%
“…MicroRNA modulates gene expression via targeting recognition the 3ʹ-untranslated region (3ʹ-UTR) of its downstream gene mRNA [ 27 ]. Previous studies showed that miR-410-3p was critically implicated in multiple human diseases [ 18 , 28–30 ]. As for cardiovascular system, available reports are limited and results seem inconsistent across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Zuo et al elegantly demonstrated the lower levels of miR-410-3p and increased the predicted target TLR2 in LPS-induced sepsis in mice, where miR-410-3p overexpression mediated TLR2 inhibition, relieving mitochondrial dysfunction and chemokine production [59]. miR-410 mimics also reduced IL6 and TNF levels in LPS-stimulated chondrocytes [60].…”
Section: Discussionmentioning
confidence: 99%